PENERAPAN METODE COOPERATIVE SCRIPT BERBANTUAN MEDIA AUDIO UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PUISI (Penelitian Tindakan Kelas di Kelas III SDN Kebonbuah Kecamatan Darmaraja Kabupaten Sumedang) - Widayanti, Siska; Sudin, Ali; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2017)
Thisresearch was conducted in third grade student of Kebonbuah elementary school. This research used classroom action research as the method. The purpose of this study is to know the description of planning, implementation, and improvement of student learning outcomes in poetry reading skills by applying cooperative script method with audio media. The initial problems experienced by students were having difficulty in reading poetry with pronunciation, intonation and proper expression. Efforts are made to improve students' ability in reading poetry, researchers will apply cooperative script method that is packaged in the form of performing and correcting games with audio media. In cycle I obtained result of 56,67% studentss complete, cycle II equal to 76,67% and at cycle III 93,33% students finish in learning poetry reading with average value 90,14. So, cooperative script method with audio media can improve students' skills in reading poetry.